Immigrant Entrepreneurship and Economic Development: A Local Policy Perspective. Issue 4 (2nd October 2019) - Huang, Xi; Liu, Cathy Yang
Abstract: Problem, research strategy, and findings: A growing number of cities, especially those outside traditional immigrant gateways, have sought to leverage immigrant resources to promote local economic development in recent years. Although some cities have explicitly included immigrant entrepreneurship as a focal area in their plans, we know little about the breadth and depth of such strategies. In this research we explore the current landscape of local small business development policies toward immigrant entrepreneurship. We conduct a detailed review of the program documents of 16 selected welcoming cities and derive 20 specific programs across five broad types: information, language, business service, financial support, and place-based approaches. Their popularity, however, varies among the case cities given the number of adoptions. For example, all 16 cities adopted information hub–related strategies, whereas only 2 considered immigrant-friendly financing programs. In comparing these policies with immigrant entrepreneurs' needs and barriers, we find their service gaps are addressed to different extents. Takeaway for practice: Here we provide a comprehensive analysis of current local government policies that aim at tapping into immigrants' entrepreneurial potential for community and economic development and their adoption levels across cities. Existing policies are able to address immigrants' information and language needs but are less targeted at developing their business skills and facilitating their access to financial capital. Place-based approaches may serve to connect immigrant-owned businesses to customers and market in the mainstream economy and thus expand their scope beyond ethnic neighborhoods. Because these programs require different levels of resources, planners and policymakers considering this agenda can assess their relative fit with local population demand in designing appropriate policies.